2021
DOI: 10.1007/s10639-021-10520-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency remote teaching during the COVID-19 pandemic: Parents experiences and perspectives

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused an emergency transform from traditional to distance learning at all levels of education, which is called emergency remote teaching. To explore parents’ views on students’ experiences of remote teaching during the COVID-19 pandemic, and their experience and perspectives toward remote teaching during the lockdown of the COVID-19 pandemic, a questionnaire was developed and distributed to parents who have at least one child who had attended a face-to-face lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(195 citation statements)
references
References 22 publications
5
140
0
12
Order By: Relevance
“…Thus, we can state that we came to similar conclusions as Lee, Ward, Chang, and Downing (2021) that parents, especially parents of the first graders, were part of the educational process, at least as a technical support. Our findings also correspond to the conclusions of Misirli and Ergulec [13]) and Parczewska [14], who found that parents play an important part in the successful implementation of education during the pandemic, although they felt incompetent to teach their children and expressed concern and anxiety about the new situation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, we can state that we came to similar conclusions as Lee, Ward, Chang, and Downing (2021) that parents, especially parents of the first graders, were part of the educational process, at least as a technical support. Our findings also correspond to the conclusions of Misirli and Ergulec [13]) and Parczewska [14], who found that parents play an important part in the successful implementation of education during the pandemic, although they felt incompetent to teach their children and expressed concern and anxiety about the new situation.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between family and school also plays an important role in the distance learning process. Recent studies of parents' experiences with education during the pandemic situation have shown that parents were burdened with school obligations like never before; moreover, they expressed they were asked for much more than they were actually capable of giving [13,14]. The excessive burden on parents has also led to increasing criticism of schools [13] and concerns about the future of their children [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Chinese parents were found to have higher expectations for academic achievement and self-directed learning after children started primary school (Lau, 2014;Lau & Ng, 2019) and thus, parents may anticipate schools to provide more online learning to continue formal education. However, parents of young children were generally found to experience great difficulties in online learning, such as prolonged screen time, lack of two-way interaction, children's low self-regulation, and insufficient time and knowledge (Dong et al, 2020;Misirli & Ergulec, 2021;Smith et al, 2016). As a result, a higher amount of learning assignments and longer duration of online learning may indicate a higher level of difficulties experienced by parents during their involvement and hence, parents may be more likely to feel dissatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…California’s COVID-19 guidelines resulted in remote education for most state K-12 schools (Bollag, 2020; Cowan, 2020). Although remote learning came with its share of complications (e.g., difficulties with face-to-face interaction with instructors, lack of traditional socialization with peers, and increased expectations for parents; Adnan & Anwar, 2020; Misirli & Ergulec, 2021), it did have a silver lining (e.g., more flexibility in children’s schedules, better parent understanding of children’s learning styles and needs, and increased remote capabilities for children with certain disabilities; Gleason et al, 2020; Roy et al, 2021). As of this writing in summer 2021, after increased access to vaccines and more COVID-sensitive infrastructure, schools in California are slowly transitioning back to in-person learning.…”
Section: Policy Backgroundmentioning
confidence: 99%